Seeking compliance nirvana. - Nolann, Greg A. (New York ACM, 2006)
Don't let SOX and PCI get the better of you
Keywords: Computing Milieux; Management of computing and information systems; General; Software; Software engineering; Management; Legal aspects of computing; Governmental issues; Regulation